2009
DOI: 10.1002/med.20146
|View full text |Cite
|
Sign up to set email alerts
|

New insights on therapy with vitamin D analogs targeting the intracellular pathways that control repigmentation in human vitiligo

Abstract: Vitiligo is a progressive depigmenting disorder affecting 0.5-2% of the population worldwide in which destruction of functional melanocytes from epidermis is a composite of multiple processes influencing melanocyte function and survival. A number of studies have recently reported that the treatment with vitamin D compounds or their combination with ultraviolet light or corticosteroids enhances repigmentation in vitiligo; however, the causal relationship at the cellular and molecular levels has not so far been … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
44
0

Year Published

2009
2009
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 43 publications
(46 citation statements)
references
References 177 publications
2
44
0
Order By: Relevance
“…In vitro studies have shown that vitamin D 3 is associated with an increase in tyrosinase activity and melanogenesis [7], which may contribute to repigmentation in vitiligo macules. Vitamin D analogues, including calcipotriol and tacalcitol, are known to enhance repigmentation in vitiligo patients [1517]. Another study reported that vitamin D exerts immunomodulatory effects by inhibiting the expression of interleukin (IL)-6, IL-8, tumor necrosis factor (TNF)-α, and TNF-γ [18].…”
Section: Discussionmentioning
confidence: 99%
“…In vitro studies have shown that vitamin D 3 is associated with an increase in tyrosinase activity and melanogenesis [7], which may contribute to repigmentation in vitiligo macules. Vitamin D analogues, including calcipotriol and tacalcitol, are known to enhance repigmentation in vitiligo patients [1517]. Another study reported that vitamin D exerts immunomodulatory effects by inhibiting the expression of interleukin (IL)-6, IL-8, tumor necrosis factor (TNF)-α, and TNF-γ [18].…”
Section: Discussionmentioning
confidence: 99%
“…The results showed sunbathing to be as effective as narrowband UVB regarding the repigmentation rate, and it required to no need to visit the clinic. Vitamin D3 alone is not clinically efficient for vitiligo irrespective of its ability to upregulate stem cell factor and endothelin-1 in vitro [2]. The combination of vitamin D3 with phototherapy yield improved results [3,4], thus the current study compared natural UV irradiation with narrowband UVB.…”
Section: Discussionmentioning
confidence: 99%
“…Activated vitamin D, 1α24(OH) 2 D 3 , is an alternative treatment for vitiligo that accelerates repigmentation through biological interaction between keratinocytes and/or fibroblast to melanocytes [2]. Narrowband UVB is commonly accepted because it provides more effective repigmentation and is less carcinogenic than broadband UVB and calcipotriol along with phototherapy is also very promising [3,4].…”
Section: Brief Reportmentioning
confidence: 99%
“…In particular, UVB induces generation of free radicals, which damage DNA. This can be ameliorated by vitamin D, which up-regulates expression of metallothionein, a free radical scavenger protein with photoprotective properties [120].…”
Section: Traumamentioning
confidence: 99%